Programma: 18 maart: modeshow m.m.v. Glanzend Vet - akrobatiek , Hoving en Hartog. . Voor Stichting Netwerk (1984)
Programma: 18 maart: modeshow m.m.v. Glanzend Vet - akrobatiek , Hoving en Hartog. Voor Stichting Netwerk.